2023
DOI: 10.3390/pharmaceutics15010185
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Treating Fields (TTFields) Induce Cell Junction Alterations in a Human 3D In Vitro Model of the Blood-Brain Barrier

Abstract: In a recent study, we showed in an in vitro murine cerebellar microvascular endothelial cell (cerebEND) model as well as in vivo in rats that Tumor-Treating Fields (TTFields) reversibly open the blood–brain barrier (BBB). This process is facilitated by delocalizing tight junction proteins such as claudin-5 from the membrane to the cytoplasm. In investigating the possibility that the same effects could be observed in human-derived cells, a 3D co-culture model of the BBB was established consisting of primary mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…TTFields therapy uses alternating electric fields with a specific frequency (100~300 kHZ) to interfere with cell mitosis, and at the same time, the electrically charged material undergoes dielectrophoresis to rupture the cell membrane and kill the tumor. Furthermore, Kessler et al showed that TTFields increase the permeability of the blood–brain barrier (BBB) by reducing the expression of tight junction proteins between neurovascular endothelial cells [ 29 ]. Kirson et al combined TTFields with TMZ and found that TTFields could improve tumor sensitivity to chemotherapy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…TTFields therapy uses alternating electric fields with a specific frequency (100~300 kHZ) to interfere with cell mitosis, and at the same time, the electrically charged material undergoes dielectrophoresis to rupture the cell membrane and kill the tumor. Furthermore, Kessler et al showed that TTFields increase the permeability of the blood–brain barrier (BBB) by reducing the expression of tight junction proteins between neurovascular endothelial cells [ 29 ]. Kirson et al combined TTFields with TMZ and found that TTFields could improve tumor sensitivity to chemotherapy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, TTFields have been proven to temporarily increase the permeability of the BBB in a human in vitro model. 61 TTField‐induced opening of BBB is similarly reversible and expands the range of intracranial drug applications.…”
Section: Anti‐tumor Mechanisms Of Ttfieldsmentioning
confidence: 99%
“… 60 Till now, the presence of BBB has posed limitations for the treatment of brain malignancies and the cerebral application of some agents. Recently, TTFields have been proven to temporarily increase the permeability of the BBB in a human in vitro model 61 . TTField‐induced opening of BBB is similarly reversible and expands the range of intracranial drug applications.…”
Section: Anti‐tumor Mechanisms Of Ttfieldsmentioning
confidence: 99%
“…16 CD41 and P-selectin have been identified on most PEV surfaces. 33 Phosphatidylserine could be found on some PEV surfaces. 34 Platelets also package mRNAs and non-coding RNAs inside PEVs to interact with other cells.…”
Section: Biology and Function Of Pevsmentioning
confidence: 99%